A treatise on corporate social responsibility non-communication - Jančič, Zlatko (Teorija in praksa, 2011)
The aim of this paper is to consider the question of the suitability of the conspicuous communication of corporate social responsibility (CSR) practices that is gaining popularity in the business world. Though it seems a plausible activity, the communication of CSR, in many cultures, might be misunderstood by various stakeholder groups as unnecessary bragging. This conceptual paper is based on the comparison between various traditions of conspicuous communication and non-communication about CSR. A critical point of view is used when discussing mainstream corporate practices in CSR marketing communication. A case study is also used to illustrate the specifics of a self-evident approach to CSR, The distaste for unnecessary bragging has its background in culture, religion, legislation and/or, as our case shows, also in ideology.
Keywords: Družbena odgovornost; Social responsibility; Communication; Komuniciranje; Slovenia; Slovenija; podjetja